Religion and The Realist Tradition. - Troy, Jodok (Routledge studies in religion and politics., 2013)
This volume picks up a rather uninvested field of international relations theory: the influence of religion on Realism as well as the power of Realism to address religious issues in world politics. Although classical scholars of Realism rarely mention religion explicitly in their well-known work, this volume suggests that Realism offers serious ground for taking religion and faith into account as well as evaluating the impact of religion on its theoretical framework: how religion and religious worldviews influence and affect the theoretical framework of Realism, and how Realism approach rel.